BONE MARROW INVOLVEMENT IN A PATIENT WITH ALPHA HEAVYCHAIN DISEASE:RESPONSE TO TETRACYCLINE TREATMENT - Zahit Bolaman; Irfan Yavasoglu; Gokhan Sargin; Gurhan Kadikoylu; Firuzan Kacar Doger (Mediterranean Journal of Hematology and Infectious Diseases)
A 28-year-old man from East Mediterranean admitted with abdominal pain, weight loss and diarrhea. Barium x-ray studies showed segmentation, dilatation of bowel loops, mucosal folds thickening and delayed intestinal transit. Histological examination of biopsy specimens revealed villous atrophy and plasmacytic infiltration limited to mucosa and submucosa. Computed tomography showed multiple lymphadenopathy in the abdomen. Serum protein electropheresis and immunoelectropheresis indicated elevated IgA concentration. Bone marrow aspiration and biopsy revealed presence of lymphoplasmacytic infiltration. Immunohistochemical analysis of the intestine, lymph nodes showed positivity for CD45, CD-79, CD-20. After tetracycline treatment the patient’s symptoms, abdominal lymphadenopathy and bone marrow infiltration disappeared and IgA concentration decreased to normal levels.